Tailored management of cavernous malformations in women: considerations and strategies—a review - Bektas, Delal; Lanzino, Giuseppe; Smith, Kelsey M.; Flemming, Kelly D. (Frontiers in Neurology, 2024)
Purpose of Review: Cavernous malformations (CM) are vascular lesions in the brain and spinal cord, characterized by clusters of endothelial-lined caverns lacking proper tight junctions. These malformations may be discovered incidentally or present with symptoms such as headaches, focal neurologic deficits, or seizures, with or without hemorrhage. This review focuses on non-surgical management considerations important for women with CM, who face challenges related to pregnancy, exogenous hormone use, anticonvulsive therapy, bone health, and mental health.Recent Findings: Emerging evidence suggests that both estrogen and progesterone may influence CM lesion behavior. Exogenous hormones, including those in oral contraceptives and oral hormone replacement therapy, indicate an elevated risk of symptomatic hemorrhage (SH) and may also influence seizure frequency and severity, particularly in women taking antiseizure medications (ASMs). Data suggest that the risk of CM hemorrhage during pregnancy is similar to the risk when not pregnant, although limitations to these studies will be reviewed.Summary: This review synthesizes the current literature on the interplay between estrogen and progesterone and CM lesion behavior, highlighting the importance of gender-and sex-specific factors in clinical decision-making. Special attention is given to the implications of exogenous hormone use, seizure management, and the psychological well-being of women with CM, underscoring the need for a multidisciplinary approach tailored to the unique needs of this patient population.• The clinical presentation, size, and location of CM in female patients are similar to men, but sex-specific hormonal influences may impact outcomes and management strategies.• The risk of CM-associated hemorrhage or seizure during pregnancy is generally low; however, careful preparation, planning, and monitoring are essential to ensure optimal outcomes for both mother and infant.• Caution is advised when considering oral exogenous estrogen and progesterone in women with CM, as these may increase the risk of SH and influence seizure activity.• Women with CM and seizure disorders should be informed about the long-term effects of ASMs, including their impact on bone health, contraceptive interactions, and potential effects on a fetus or breastfed infant.• Addressing mental health is as important as managing physical health in women with CM, requiring comprehensive care.